Classifying and mapping rainfall seasonality in South Africa: a review. Issue 2 (4th May 2019) - Roffe, S.J.; Fitchett, J.M.; Curtis, C.J.
ABSTRACT: Across South Africa, many activities warrant consistent and predictable rainfall patterns which can be achieved from classification of rainfall seasonality into homogeneous zones. Since the first seasonality map for South Africa which was published in 1938, attempts to classify and map rainfall seasonality for the region has proliferates, with many different approaches adopted. Currently, 59 published maps depicting rainfall seasonality across South Africa are known. Although the dichotomy between the summer and winter rainfall zones is well-reported, classification and mapping of the seasonal rainfall zones remains somewhat arbitrary and relatively inconsistent amongst authors. Amongst these maps, there is a broad consensus that three distinct regions with a relatively homogenous seasonal distribution of rainfall exist, known as: summer, winter and year-round rainfall zones. Much of the country has been classified with at least 75% spatial agreement, while classification for the remainder of the country remains rather disputed. Available classification approaches were interrogated, and it was demonstrated that each approach is associated with limitations affecting the accuracy of these maps. We suggest a rigorously assessed approach, or a set of approaches should be used to classify rainfall zones which may be important in further understanding rainfall seasonality across South Africa.